P 155 First evidence for glial pathology in late life minor depression – S100B is increased in males with minor depression – results form LIFW-adult study. Issue 10 (October 2017) - Polyakova, M.; Sander, C.; Arelin, K.; Lampe, L.; Luck, T.; Kratzsch, J.; Hoffmann, K.T.; Riedel-Heller, S.G.; Schönknecht, P.; Schroeter, M.
Abstract : Background: Minor depression is as ubthreshold depressive disorder. It is diagnosed when a patient suffers from 2 to 4 depressive symptoms for at least 2 weeks. Though minor depression affects nearly ten percent of the elderly population, its pathophysiology has hardly been investigated. In our study we assessed serum levels of biomarkers for plasticity, glial and neuronal function: brain-derived neurotrophic factor (BDNF), S100B and neuron specific enolase (NSE). Methods: 27 subjects with minor depressive episode and 82 healthy subjects, 60–79 years old, were selected from the database of the Leipzig population-based study of adults (LIFE-adult). Serum levels of BDNF, S100B and NSE were compared between groups, and correlated with age, body-mass index (BMI), and degree of white matter hyperintensities (calculated as a score on Fazekas scale). Results: S100B was significantly increased in males with minor depression in comparison to healthy males, whereas other biomarkers did not differ between groups ( p  = 0.10–0.66). S100B correlated with BMI (rs = 0.246, p  = 0.031) and with age in healthy subjects (rs = 0.345, p  = 0.002). NSE correlated with Fazekas score in patients with minor depression (rs = 0.436, p  = 0.048) and in the whole sample (rs = 0.252, p  = 0.019). Discussion: For the first time we assessed serum levels of BDNF, S100B and NSE in late life minor depression. We found evidence for increased biomarker for glial activation S100B. Increased S100B in males with minor depression, without alterations in BDNF and NSE, support the glial hypothesis of depression. According to this hypothesis glial alterations precede neuronal changes in depression. Correlation between white matter hyperintensities and NSE underscores the vascular hypothesis of late life depression.